Mediating Role of Burnout Between the Job Demands-Control Model and Psychological Well-being in Healthcare Professionals in Pakistan - Siddiqui, Hareem; Sharif, Faiza; Ahmed, Ambreen; Akbar, Waqar (UI Scholars Hub, 2021)
Integrating the Job Demand-Control model (JDC) with the Conservation of Resource Theory, this study tested the JDC model for the direct and indirect effects of job demands (JD) and control (JC) on the psychological well-being (PWB) of healthcare professionals working in hospitals in Karachi, along with the mediating effects of burnout. The study employed Structural Equation Modelling using SMART PLS for data analysis of a sample of 316 healthcare providers from different hospitals in Karachi. The results supported the direct effects of JD and JC on PWB and the mediating effects of burnout The findings of the study add further empirical evidence to current literature on job stress. The results indicated that healthcare professionals in Pakistan are confronted with a demanding job that causes burnout and ultimately becomes a reason for their decreased PWB. The study also presented various practical implications for different stakeholders. From a sustainability standpoint, this study indicated the need to balance job demands and job control in order to design psychologically healthy jobs.